Web atmospheric qualities in luxury fashion brand web sites. Issue 4 (14th September 2015) - Kim, Hyeonsoo; Choi, Yun Jung; Lee, Yuri
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the relationship between atmospheric qualities with different levels of task relevance in luxury fashion brand web sites and their impact on consumer attitude toward the site and brand, which is essential to build valid strategies for e-retailing. Design/methodology/approach – An empirical study was conducted and quantitative analyses of 292 respondents' shopping experiences yielded findings that confirm the impact of atmospherics upon the shopper's views of the web site and the brand. Structural equation modeling was used to test the research hypotheses. Findings – Both low task-relevant atmospherics (web site design, responsive customer service) and high task-relevant atmospherics (product information, convenience) affect the consumers' revisit intentions toward the web site, while web site design directly affected brand attitude. The study also illustrates the mediating roles of product information and convenience to the relationships between web site design and responsive customer service and the consumers' revisit intentions toward the site. Practical implications – This study provides insights for luxury e-tailing. Luxury e-tailers should understand the different effects depending upon the types of web atmospheric qualities and use them strategically. Originality/value – The main contribution of the study is to highlight the unique aspects of luxury online shopping in the Korean context. This study also contributes to e-commerce research by providing an expanded understanding of the interrelationship between types of web atmospheric qualities.